How small and medium sized enterprises (SMEs) can influence the successfulness of a partnership with a large company (LCO) in the technology innovation sector - Oerlemans, Leon A.G. (University of Pretoria, 2013)
Thesis (PhD (Technology Management))--University of Pretoria, 2007.